Prevalence and risk factors of multi drug resistant tuberculosis in children - Aslam, Hira; Asif Hanif; Usman Rasool (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the prevalence of drug-resistant tuberculosis and to identify possible risk factors in children. Method: The descriptive, interview-based study was conducted at the Pulmonology outdoor clinic of Jinnah Hospital, Lahore, Pakistan, from January to August 2019, and comprised children aged up to 14 years who were either contacts of a multi-drug resistant tuberculosis patients or non-contacts. Data related to their demography as well as clinical and social characteristics was collected using a questionnaire. Data was analysed using SPSS version 22. Results: Of the 202 subjects, 115(56.9%) were girls and 87(43.1%) were boys. There were 70(34.7%) subjects aged >13 years, followed by 45(22.3%) aged 9-12 years, 44(21.8%) aged <=4 years and 43(21.3%) aged 5-8 years. Overall, there were 26(12.9%) cases positive for multi-drug resistant tuberculosis; 16(61.5%) girls and 10(38.5%) boys. In terms of age, 17(65.4) cases were positive in those aged >13 years. Age, previous history of tuberculosis, co-infection with any immune-compromising disease and close contact with patients of multi-drug resistant tuberculosis were significant risk factors identified. Conclusion: The prevalence of multi-drug resistant tuberculosis was high in contacts of multi-drug resistant pulmonary tuberculosis patients, more prevalent in children aged 13-14 years. Key Words: Mycobacterium tuberculosis, MDR in children, multi-drug resistance, MDR TB contacts.